Circulating T cell subpopulations in dairy calves infected with Bovine viral diarrhea virus 2 and Bovine herpes virus 1 following modified-live virus booster vaccination: Effects of the administration route and trace mineral supplementation - Hoyos Jaramillo, Alejandro; Palomares, Roberto A.; Bittar, João H.J.; Hurley, David John; Rodríguez, Adriana; González Altamiranda, Erika; Kirks, S.J.; Gutierrez, Alberto; Wall, S.; Miller, K.; Urdaneta, J.; Skrada, Katie A.; et al. (Elsevier, 2025)
The objective of this study was to evaluate the effects of the vaccine administration route and the concurrent use of injectable trace minerals (ITM) with booster vaccination on the circulating leukocyte counts and T cell subpopulations in dairy calves challenged with Bovine viral diarrhea virus 2 (BVDV2) and Bovine herpes virus 1 (BHV1). A total of 60 Holstein male calves were used in this study. Forty-eight calves were administered a MLV intranasal (IN) vaccine containing BHV1, BRSV, BPI3V (Inforce 3®), and randomly assigned to subcutaneous (SC) administration of injectable trace minerals (ITM, n = 24) or saline (SAL, n = 24). Ten weeks later, the calves received booster vaccination using either SC or IN route and a second dose of ITM, or saline, according to previous groups [ITM-SC (n = 12), ITM-IN (n = 12), SAL-SC (n = 12), and SAL-IN (n = 12)]. Additionally, 12 calves did not receive vaccine or treatment (UNVAC, n = 12). Seven weeks after booster all calves were challenged with BVDV2 and seven days later with BHV1. Blood samples were collected on days −7, 0, 3, 6, 7, 10, 12 and 14 for determination of leukocyte counts and T cell subpopulations (CD4+, CD8+, WC1+ and CD25+). Unvaccinated calves had a significant leukopenia, compared to the vaccinated calves. There was a significant decrease of CD4+ CD8+ T cells over time after BVDV2 challenge, being more pronounced in the UNVAC calves. Calves receiving SC vaccination appeared to have greater CD4+ T cell number compared to the UNVAC calves. Calves treated with ITM had greater CD8+ T cells count than the other groups. Calves in the ITM-IN group had the greatest CD8+ T cell count on days 6 and 7 (P < 0.01). All vaccinated groups had steady response of CD4+CD25+ T cells and a slight increase of CD8+CD25+ T cells. In contrast, UNVAC calves had a significant increase of CD4+CD25+, CD8+CD25+ and WC1+CD25+ T cells on day 14. In conclusion, vaccine administration route and use of injectable trace minerals concurrent with vaccination affected the number CD4+ and CD8+ T cells in response to BVDV2 +BHV1 infection. Trace minerals supplementation concurrent with MLV vaccination might generate an improved cellular immunity against viral infections involved in respiratory disease.